Morphometric and meristic analysis of bluespotted mudskipper, boleophthalmus boddarti (Pallas, 1770) from selected mangrove areas in peninsular malaysia / Syazwin Rafhanah Saifuzzaman - Saifuzzaman, Syazwin Rafhanah (2018)
Mudskippers are locally known as Belacak or Tembakul has unique adaptations that can make them live in the land. Mudskippers are usually found at the area of mangrove site. 72 individuals of mudskippers were collected from three selected mangrove areas in Peninsular Malaysia; Matang Perak, Pendas Johor and Pekan Pahang. A total of 17 morphometric characteristic and seven meristic measurements were measured on the sample. The means of the each characteristic were estimated by using analysis of Variance (ANOVA) with P<0.05. The regression analysis was carried out for information in the relation of the total length and weight of the mudskipper. The length and weight relationship for B. boddarti from Pendas Johor is described as log W= 3.116 log TL-5.280, while Matang Perak is log W= 3.297 log TL-5.650 and Pekan Pahang is log W= 2.877 log TL-4.780. Mudskipper from each of the population displayed different intensity of coloration. This shows that the intensity of the coloration cannot be used to differentiate the species from the different places as mudskipper adapts their coloration with its environment.